PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PENIPUAN LOWONGAN KERJA PARUH WAKTU (FREELANCE) DI MEDIA SOSIAL - Alkhonsa, Nurfaijah; Asphianto, Aan; Rofiana, Reine (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2025)
The development of information technology has opened up new economic opportunities, including in the form of part-time jobs offered online. However, on the other hand, this has also been exploited by irresponsible parties to commit fraud using increasingly complex methods. The rampant part-time job scams on social media using commission and deposit schemes have caused significant losses to the public, especially job seekers. Although there are criminal laws and regulations related to electronic information, legal protection for victims has not been effectively implemented. This study aims to analyze the forms of legal protection available to victims of job scam fraud on social media and identify preventive measures that can be implemented comprehensively. This study employs a normative legal approach with qualitative analysis, examining secondary data from legislation (Article 378 of the Criminal Code, Article 492 of the New Criminal Code, Article 28(1) of the Electronic Information and Transactions Law), literature, and interviews with the Cyber Crime Unit of the Banten Provincial Police. This research is supported by legal protection theory and crime prevention theory. The results of the study indicate that legal protection for victims is inadequate because the focus of regulations is only on punishing perpetrators, without mandatory restitution mechanisms, psychological counseling, or effective access to justice. Limitations in digital forensics and inter agency coordination also hinder efforts. Penal prevention efforts (punishment via the Criminal Code and the ITE Law) are ineffective due to the anonymity of perpetrators, while non-penal approaches such as digital literacy and cyber patrols remain limited in scope. This study recommends revising regulations to mandate restitution, strengthening the role of the LPSK, fostering cross-sectoral collaboration, and launching digital literacy campaigns to create a safe digital ecosystem that prioritizes victims.